Macroeconomic uncertainties, prudent debt targets and fiscal rules - Fall, Falilou (OECD Publishing, 2015)
The sharp rise in debt experienced by most OECD countries raises questions about the prudent debt level countries should target. It also raises questions about the fiscal frameworks needed to reach them and to accommodate cyclical fluctuations along the path towards a prudent debt target. The objective of this paper is to define long-run prudent debt targets for OECD countries and country-specific fiscal rules. To this end, a semi-structural macroeconomic model for OECD countries and primary balance reaction functions are estimated. The shocks derived from these estimations are used to assess uncertainties surrounding the development of macroeconomic variables. The model is simulated up to 2040 to derive the prudent debt target for each country and design country-specific fiscal rules
Keywords: Economics